Design of a novel dual-band microstrip patch antenna operating at 2.45 GHz and 2.84 GHz with practical implementation - Mallik, Anik; Kundu, Sanjoy (16th Int'l Conf. Computer and Information Technology, 2014)
This paper presents the design and analytical studies of a novel dual-band microstrip patch antenna operating at two frequencies of ISM bands: 2.45 GHz and 2.84 GHz. The necessity for multiband antennas is increasing with the demand of wireless communications and as a result, light-weight, low-volume and low-profile microstrip patch antennas have been nourished by the researchers which initiated our design of this proposed antenna. This antenna is characterized well with its parameters i.e. Reflection coefficient (below -10 decibels), voltage standing wave ratio (VSWR) (about 1.5), forward gain (above 8.07 decibel with compared to isotropic antenna), radiation pattern etc. which are shown in this paper. The antenna was designed in Numerical Electromagnetic Code (4nec2) design environment and simulated for the antenna parameters. Then it was practically implemented and tested with WATS-2002 (wave and antenna training system). The simulated and tested results show that this antenna is eligible for short range communication like Bluetooth, WLAN, Wi-Fi and so on. This antenna is highly directive, matched with 50 ohms feeding line impedance and has uniform radiation over all the directions, but has a low bandwidth for each of the two bands which can be improved with a modification in the structure and the frequency bands can be changed by adding some parasitic elements.